Extraterrestrial electrochemistry. (December 2018) - Schilter, David
Martian sediments and meteorites contain a complex mixture of inorganic and organic materials. The identities and localizations of these species point to a mechanism of organic synthesis that begins with the electrochemical reduction of carbon dioxide.